Electron and nuclear dynamics following ionisation of modified bismethylene-adamantane. (14th September 2016) - Vacher, Morgane; Albertani, Fabio E. A.; Jenkins, Andrew J.; Polyak, Iakov; Bearpark, Michael J.; Robb, Michael A.
Abstract : We have simulated the coupled electron and nuclear dynamics using the Ehrenfest method upon valence ionisation of modified bismethylene-adamantane (BMA) molecules where there is an electron transfer between the two π bonds. We have shown that the nuclear motion significantly affects the electron dynamics after a few fs when the electronic states involved are close in energy. We have also demonstrated how the non-stationary electronic wave packet determines the nuclear motion, more precisely the asymmetric stretching of the two π bonds, illustrating "charge-directed reactivity". Taking into account the nuclear wave packet width results in the dephasing of electron dynamics with a half-life of 8 fs; this eventually leads to the equal delocalisation of the hole density over the two methylene groups and thus symmetric bond lengths.